Health-related quality of life and ego integrity among the oldest old – Evidence from the multicenter AgeCoDe-AgeQualiDe study. (July 2021) - Hajek, André; Forstmeier, Simon; Brettschneider, Christian; Lühmann, Dagmar; Döhring, Juliane; Wiese, Birgitt; Oey, Anke; Weyerer, Siegfried; Werle, Jochen; Pentzek, Michael; Fuchs, Angela; Röhr, Susanne; et al.
Highlights: Investigating the link between health-related quality of life and ego integrity. Data were derived from a multicenter prospective cohort-study (oldest old). Widely established instruments were used (e.g., EQ-5D-3 L). Findings stress the importance of health-related quality of life for ego integrity. Abstract: Purpose: To investigate the association between health-related quality of life and ego integrity among the oldest old. Materials and methods: Cross-sectional data were taken from follow-up wave 9 of the multicenter prospective cohort study "Needs, health service use, costs and health-related quality of life in a large sample of oldest-old primary care patients (85+)" (AgeQualiDe). Our analytical sample comprised n  = 495 observations. Mean age was 90.2 years (SD: 2.7 years). Health-related quality of life was quantified using the EQ-5D-3L questionnaire (including the visual analogue scale EQ-VAS). Ego integrity was measured using the Ego Integrity Scale. Results: Regressions showed an association between decreased ego integrity and problems with 'usual activities', 'pain/discomfort' and 'anxiety/depression'. Furthermore, regressions showed a marginally significant association between decreased ego integrity and problems with 'mobility' and a decreased EQ-VAS score. Ego integrity was not significantly associated with problems with 'self-care'. Conclusions: Findings stress the importance of health-related quality of life for ego integrity among the oldest old. Future studies are required to clarify the underlying mechanisms.